2016
DOI: 10.1016/j.ijhydene.2016.07.067
|View full text |Cite
|
Sign up to set email alerts
|

A high performance electrode material for lithium ion batteries derived from a cobalt-based coordination polymer

Abstract: A carbon rich coordination polymer, [Co(fa)(bpy)] n (1), based on formic acid (fa) and an auxiliary ligand 4,4`-bipyridine (bpy) is utilized as a single source precursor to an exceptional lithium-ion battery electrode material. Compound 1 consists of cobalt-formate chains connected via bipyridine ligands into a three dimensional lattice. A cobalt-oxide/carbon composite material is obtained by the controlled carbonization of 1 at 900 °C. Morphological, structural, and chemical analysis of the composite is carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Garnering considerable attention under the predicament of energy crisis, the lithium-ion batteries (LIBs), which are applied in electric vehicles and portable electronics, imperatively require to achieve a high energy density. One of the most crucial points of enhancing the energy density of LIBs is how to develop the favorable cathode materials with a higher specific capacity and work voltage. Currently, lithium-rich manganese-based layered oxides (LRMOs) have emerged from diverse amounts of traditional cathode materials due to their high working voltage and specific capacity (>250 mAh g –1 ). In addition, it has been well identified that the remarkable capacity of LRMOs arises from the synergistic effect of anions and cations in hybrid redox reactions, which delivers the compensatory extra charge/ion exchange. , Simultaneously, the redox of anions (e.g., oxygen) during cycling also makes an adverse difference, namely, voltage decay, which impedes their wide-scale commercial application. Cobalt, which is one of the most important elements within ternary cathode materials, has been broadly regarded as a contributor to stabilizing the material structure and optimizing the cycling and rate performance.…”
Section: Introductionmentioning
confidence: 99%
“…Garnering considerable attention under the predicament of energy crisis, the lithium-ion batteries (LIBs), which are applied in electric vehicles and portable electronics, imperatively require to achieve a high energy density. One of the most crucial points of enhancing the energy density of LIBs is how to develop the favorable cathode materials with a higher specific capacity and work voltage. Currently, lithium-rich manganese-based layered oxides (LRMOs) have emerged from diverse amounts of traditional cathode materials due to their high working voltage and specific capacity (>250 mAh g –1 ). In addition, it has been well identified that the remarkable capacity of LRMOs arises from the synergistic effect of anions and cations in hybrid redox reactions, which delivers the compensatory extra charge/ion exchange. , Simultaneously, the redox of anions (e.g., oxygen) during cycling also makes an adverse difference, namely, voltage decay, which impedes their wide-scale commercial application. Cobalt, which is one of the most important elements within ternary cathode materials, has been broadly regarded as a contributor to stabilizing the material structure and optimizing the cycling and rate performance.…”
Section: Introductionmentioning
confidence: 99%